ANALYSIS OF THE EFFECT OF THE TOURISM SECTOR ON THE ESTABLISHMENT OF MULTIPLIER OUTPUT AND MULTIPLIER INCOME DURING THE COVID-19 PANDEMIC IN CENTRAL JAVA - Nanang Yusroni; Umar Chadhiq (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Tourism activities in Central Java in recent years have increased. In the long term, where the tourism sector is expected to be the prima donna in development, a more intensive and comprehensive study needs to be carried out considering other development sectors which directly or indirectly have a large influence on tourism development. Likewise with tourism activities in Central Java Province which has been designated as one of the main tourist destinations in Indonesia. The data used is secondary data, especially from the input-output table of Central Java Province in 2016 and tourist expenditure data. From the research, it was found that tourist spending in Central Java Province had an impact on increasing sectoral output although with a relatively small increase. However, because the impact of tourist spending on output and indirectly created employment opportunities is greater, the impact of tourism on the economy is very dynamic and has long-term prospects. Keywords: Tourism Sector, output multiplier. Income multiplier, input-output model.